Analisis Preservasi Arsip Statis di Dinas Perpustakaan dan Kearsipan Kabupaten Labuhanbatu - Putri Septiani; Abdul Karim Batubara; M. Nasihudin Ali (Lembaga Pengembangan Kinerja Dosen, 2024)
The aim of this research is to find out more about the Labuhanbatu Regency Library and Archives Service's approach to static archive preservation, as well as the challenges faced and the steps taken to overcome them. To ensure the security and protection of archives, static archive preservation is carried out. This type of research uses qualitative descriptive techniques. This research uses the Miles & Huberman data analysis approach, which specifically focuses on data reduction, data presentation, and drawing conclusions. Through observation, interviews, and documentation, researchers collect information for data analysis. Two people participated in this research as informants. Using a purposive sampling approach, these informants were selected from among those who met the requirements of the research subjects, namely, archivists who had knowledge of archival preservation. The research findings show that although the static archive preservation of the Labuhanbatu Regency Library and Archives Service is good, it still does not meet the expectations of the theory that guides the research. Archives activists are of the opinion that despite their best efforts, archives are still not optimally maintained due to various obstacles, including inadequate funding, inadequate facilities and infrastructure, and human resources who do not understand archives. Efforts made by archivists include providing special archival training on archival science, building inadequate facilities and infrastructure with allocated funds, and prioritizing the use of the budget for crucial tasks to achieve archive maintenance in good condition.